Analysis of inorganic in low explosive residue using solid phase extraction as a pre-concentration technique - Mahmod, Anizah (2016)
Solid Phase Extraction (SPE) is a very powerful technique for clean-up and pre-concentration of the sample. Even though there is no universal method for SPE, there have been an increasing demand for a reliable and accurate forensic trace analysis. Samples received by a forensic laboratory are often in small amounts and there is a need to develop methods that are capable to detect lower concentration. The objectives of this study were to develop, evaluate and compare an SPE procedure as a pre-concentration step with conventional cotton swabbing method for analysis of ions in explosive residue. Four samples of pyrotechnics were analysed in this study. The samples were Mercun Bola (MB), Mercun Ketupat (MK), Happy Bomb (HB) and Monster Bomb (MS). The results of this study showed that all six standard cations (lithium, sodium, ammonium, potassium, magnesium and calcium) were successfully separated within 45 minutes using Metrosep C4 column (250 x 4 mm i.d) with 5 µm particle size. The eluent used were 0.7 mmol/L dipicolinic acid and 1.7 mmol/L nitric acid with a flow rate of 1.0 mL/min and pressure of 9.5 MPa. The calibration graph gave a good linearity with r2 = 0.992. The detection limits were 0.32 µg/L to 1.32 µg/L and quantitation limits in the range of 1.26 µg/L to 4.4 µg/L. The SPE method was optimized using several parameters before the method was applied to post-blast residues. The SPE cartridge used was Supelco MCAX with 500 mg sorbent bed packed with sulfonilic functional group. The SPE parameters that have been chosen were sample flow rate, type of eluents and volume of eluent. The results indicated that SPE procedure gave good pre-concentration of the analytes of interest with the preconcentration factor in the range of 7 to 74.